TO’G’AY MUROD ASARLARIDAGI SHEVAGA OID SO’ZLARNING FONETIKASI - ESHBOYEV ABROR RAXMATULLA O’G’LI, D.A.Ergasheva (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
The article is typical of the dialect used in Togay Murad's stories phonetic, lexical and morphological characteristics of words are explained. Writer from the methods of transfer of meaning used by the dialectics involved in his works examples are given.